Functionalized graphene quantum dots for dye-sensitized solar cell: Key challenges, recent developments and future prospects. (July 2021) - Mahalingam, Savisha; Manap, Abreeza; Omar, Azimah; Low, Foo Wah; Afandi, N.F.; Chia, Chin Hua; Rahim, Nasrudin Abd
Abstract: One of the pioneering materials nowadays is graphene quantum dot (GQD), which possesses outstanding electrical, thermal, and mechanical properties followed by less toxicity and robust photoluminescence. These commendable properties allow GQD to be suitable enough to apply in dye-sensitized solar cells, incapacitating current material limits. Nevertheless, pure GQDs have many challenges in reaching their full potential in DSSC. Chemical modification and functionalization tune the physical and chemical properties, driving GQD towards high-performance DSSC. This is an ideal way of modifying GQD because the chemical adsorption of atoms or molecules prevents the destruction of the carbon network without substitutional impurities. Here, we deliver a short outline of progress in understanding GQD functionalization from theoretical/computational perspectives. This chemically modified GQD is then linked with the performance of DSSC. The review also summarizes the electron transport in GQD-DSSC to minimize back-electron transmission recombination at the photoelectrode/electrolyte edge. The impact, outlook, and future prospects of the GQD-DSSC are included as a conclusion in this review. Graphical abstract: Image 1 Highlights: Interaction of chemical functionalization with GQD. Role of functionalized GQD in various DSSC components such as photoelectrode, sensitizer, electrolyte, and counter electrode. Key challenges for high-performance GQD-DSSC. Electron transport and performance review of GQD-DSSC. Impact and future prospects for GQD-DSSC and recommendations for DSSC-performance enhancement.